High-Molecular-Weight Hyaluronic Acid Vehicle Can Deliver Gadolinium Into the Cochlea at a Higher Concentration for a Longer Duration: A 9.4-T Magnetic Resonance Imaging Study - Hwang, Yu-Jung; Park, Mina; Park, Moo Kyun; Lee, Jun Ho; Oh, Seung Ha; Suh, Myung-Whan (Frontiers in Neurology, 2021)
Intratympanic (IT) gadolinium (Gd) injection is one method of delivering Gd into the inner ear to evaluate the amount of endolymphatic hydrops (EH) using magnetic resonance imaging (MRI). As Gd is usually prepared in a fluid form mixed with saline, Gd injected into the middle ear drains easily through the Eustachian tube within several hours. High-molecular-weight (hMW) hyaluronic acid (HA) is an ideal vehicle for IT Gd due to its viscous and adhesive properties. The present study was performed to elucidate whether novel hMW HA is superior to conventional HA in delivering Gd into the inner ear in the short term. The second aim was to verify the long-term Gd delivery efficiency of hMW HA compared to the standard-of-care vehicle (saline). IT Gd injection and 3D T1-weighted MRI were performed in 13 rats. For the short-term study (imaging after 1, 2, and 3 h), the left ear was treated with hMW HA+Gd and the right ear with conventional HA+Gd. For the long-term study (imaging after 1, 2, 3, and 4 h, 1 – 3 days, and 7 – 10 days), the left ear was treated with hMW HA+Gd and the right ear with saline+Gd. Signal intensities (SIs) in the scala tympani (ST) and scala vestibuli (SV) were quantified. Compared to conventional HA, signal enhancement was 2.3 – 2.4 times greater in the apical and middle turns after hMW HA+Gd injection (SV at 1 h). In comparison to the standard-of-care procedure, the SI was not only greater in the short term but the higher SI also lasted for a longer duration. On days 7 – 10 after IT Gd delivery, the SI in the basal turn was 1.9 – 2.1 times greater in hMW HA+Gd-treated ears than in saline IT Gd-treated ears. Overall, hMW HA may be a useful vehicle for more efficient IT Gd delivery. Gd enhancement in the cochlea improved approximately two-fold when hMW HA was used. In addition, this greater enhancement lasted for up to 7 – 10 days. Repeated MRI of EH may be possible for several days with a single IT hMW HA+Gd delivery.